Three-Dimensional Placement and Transmit Power Design for UAV Covert Communications - Zhou, Xiaobo; Yan, Shihao; Ng, Derrick Wing Kwan; Schober, Robert (IEEE transactions on vehicular technology, 2021)
This work tackles the joint optimization of a unmanned aerial vehicle's (UAV's) three-dimensional (3D) placement and transmit power for covert communications with the objective to maximize the communication covertness subject to a constraint on communication quality. We analytically prove that the optimal horizontal location of the UAV must be on the straight line connecting the legitimate receiver and the warden, while its optimal height is the minimum allowable flying altitude. Subsequently, we derive closed-form expressions to characterize the UAV's optimal 3D location and its optimal transmit power, taking into account the impact of finite blocklength coding. Our numerical results show that the developed optimal design can achieve a better covertness performance compared with an optimal two-dimensional (2D) UAV deployment, especially when the warden is close to the receiver. Besides, we show that, for a given requirement on the communication quality, communication covertness does not always improve as the number of channel uses increases.